Evaluation of rapid, commercial latex techniques for serogrouping beta-hemolytic streptococci. - Daly, J A (1988)
The clinical need to rapidly and correctly differentiate beta-hemolytic streptococci into Lancefield groups has prompted the development of commercially available rapid agglutination techniques. A modified Streptex (Wellcome Diagnostics, Research Triangle Park, N.C.) technique and the PathoDx latex Strep Grouping Kit (Diagnostic Products Corporation, Los Angeles, Calif.) technique were applied to 220 strains of beta-hemolytic streptococci that were serologically grouped by standard techniques. Agreements between standard and modified Streptex and PathoDx techniques were 99.1 and 100%, respectively. Modified Streptex produced a false-negative for one group G isolate and a weak-positive reaction for a group G reagent with a nongroupable isolate. Sixty-five strains representative of bacteria that may be found in the posterior pharynx in concentrations high enough to cause potential reactions with antigen detection reagents were tested with Streptex and PathoDx reagents. No cross-reactions were observed with any reagent tested when challenged with these 65 strains. When combined with colonial morphology and hemolytic reaction, both modified Streptex and PathoDx were rapid, specific tests for identifying streptococci, with PathoDx being slightly faster.